An unusual mortality event for bottlenose dolphins links to altered diets resulting from ecological changes - Stolen, Megan K.; Durden, Wendy Noke; Jablonski, Teresa; Worthy, Graham A. J.; Paperno, Richard; Jacoby, Charles A. (Frontiers in Marine Science, 2025)
Bottlenose dolphins (Tursiops truncatus) often have served as sentinel species for ecological changes in estuarine and marine systems. In 2013, the population of bottlenose dolphins in the Indian River Lagoon exemplified this role because an unusual mortality event involving malnourishment followed ecological changes. Potential causes of mortalities were investigated using surveys of key habitats and abundances of potential prey, stable isotope ratios from dolphins and potential prey, estimations of energy densities for key types of prey, and surveys of environmental conditions. The ecology of the lagoon changed substantially after 2011, with shading by intense, extensive, and long-lasting blooms of phytoplankton resulting in a > 50% decrease in the mean cover of seagrass and a > 75% decrease in mean biomass of drifting macroalgae. These reductions in key structural habitats preceded changes in ratios of stable carbon and nitrogen isotopes in samples of muscle from stranded dolphins. Changes in isotopic ratios indicated 9–25% increases in consumption of Archosargus rhomboidalis (sea bream) and 14–20% decreases in consumption of Elops saurus (ladyfish). The changes in diet reflected availability of prey, with a fisheries independent monitoring program yielding parallel changes in catches of sea bream and ladyfish. The dietary shift may have contributed to the 2013 unusual mortality event because sea bream yielded a lower mean energy density than ladyfish. Additionally, below average temperatures in 2010 and 2011 may have stressed some dolphins, particularly those that were garnering less energy from their diet. In contrast, osmotic stress was unlikely, given increasing salinities in the system. Overall, the results provided an example of links from blooms of phytoplankton to changes in habitat, availability of prey, and diets of dolphins followed by an unusual number of mortalities. Loads of nutrients that fueled the blooms are being reduced, with safe loads scheduled to be reached in 2035 and recognition that additional, adaptive efforts may be necessary to obviate harmful algal blooms.